TEACHER'S POLITENESS IN EFL CLASS - Ayfer Sülü (Informascope, 2015)
Politeness is considered to promote effective interaction between people. In the context of language teaching, it is believed to enhance learning by providing a lively and friendly atmosphere in classroom (Jiang, 2010). This study investigates an EFL classroom in terms of interaction between English learners and a native English speaking teacher. The aim of the study is to see whether the effects of politeness strategies differ when students and teacher do not share the same culture and native language. Two hours of classes were observed and tape-recorded by the researcher. The recordings were transcribed and analyzed by making use of related politeness strategies and functions of speech. Also, three randomly chosen students were interviewed after the class. The findings showed that politeness existed in that EFL classroom and it helped students to have positive feelings towards the lesson and motivated them to participate more in classes.